Accepting the robotic other: Why real dolls and spambots suggest a near-future shift in architecture's architecture. (March 2016) - Webb, Alexander
With weak Artificial Intelligence in the pockets of the majority of American adults, a societal introduction of a strong Artificial Intelligence or sentience seems close. Although the "intelligence" of our phones' intelligence can be laughably brittle, the learning capacity demonstrated by the Internet of Things suggests more robust intelligence is on the way, and some would say it has already arrived. Several private technology firms have asserted that a robust Artificial Intelligence already exists and thought leaders within computation are lining up to ensure that it is not evil. Regardless of the morality of Artificial Intelligence, if our charge as architects is to design occupiable space, then we need to consider post-anthropocentric ecologies as well as how to adapt our design strategies to reflect inclusion of other species. This article describes two linked lines of thought, a meditation on the pending societal inclusion of the robotic other and why that robotic sentience may arrive from an unexpected origin and can reshape how we conceive of architecture itself.